ALEMTUZUMAB PERSISTENTLY SLOWS BRAIN VOLUME LOSS IN RRMS. Issue 12 (15th November 2016) - Coles, Alasdair; Arnold, Douglas; Barkhof, Frederik; Filippi, Massimo; Hartung, Hans-Peter; Havrdova, Eva; Selmaj, Krzysztof; Margolin, David; Thangavelu, Karthinathan; Schippling, Sven; ,
Abstract : Patients with active relapsing-remitting MS (RRMS) who were treatment-naive (CARE-MS I; NCT00530348 ) or with inadequate response (≥1 relapse) to prior therapy (CARE-MS II; NCT00548405 ) demonstrated improved efficacy with alemtuzumab versus subcutaneous interferon beta-1a over 2 years, including slowing of brain volume loss (BVL). Here we examine alemtuzumab's effect on BVL over 5 years. Patients who received alemtuzumab at baseline and Month 12 in the core studies could enter an ongoing extension (NCT00930553 ), receiving as-needed alemtuzumab retreatment for disease activity. MRI scans were acquired at baseline and annually. BVL was measured by relative brain parenchymal fraction change. 349 (95%) CARE-MS I and 393 (93%) CARE-MS II alemtuzumab patients entered the extension. Of those, 68% and 60% received no alemtuzumab since Month 12; 98% and 92% received no other disease-modifying therapy. Median yearly BVL decreased over 4 years in CARE-MS I, remaining low in Year 5 (Year 1: −0.59%, Year 2: −0.25%, Year 3: −0.19%, Year 4: −0.15%, Year 5: −0.20%). The pattern was similar in CARE-MS II (Year 1: −0.48%, Year 2: −0.22%, Year 3: −0.10%, Year 4: −0.19%, Year 5: −0.07%). Slowing of BVL with alemtuzumab was maintained over 5 years, despite most patients not receiving treatment for 4 years.